The black and its double : the crisis of self-representation in protest and 'post'-protest black South African fiction - Kenqu, Amanda Yolisa (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2015)
This study explores the crisis of representation in black South African protest and 'post'-apartheid literature. Conversant with the debates on the crisis of representation in black South African protest literature from the 1960s to the late 1980s, the dissertation proposes a re-reading of the 'crisis' by locating it in the black writer's struggle for an aesthetic with which to express the existential crisis of blackness. I contend that not only protest but also contemporary or 'post'-protest black South African literature exhibits a split or fractured mode of writing which is characterised by the displacement/unheimlichheid produced by colonialism and apartheid, as well as by the contentious nature of that which this literature endeavours to capture "“ the fraught identity of blackness. In my exploration of the split or double narratives of Mongane Serote's To Every Birth Its Blood, K. Sello Duiker's Thirteen Cents, and Kopano Matlwa's Coconut, I examine the representation of blackness through the themes of violence, trauma, powerlessness, failure, and unhomeliness/unbelongingness "“ all of which suggest the lack of a solid foundation upon which to construct a stable black identity. This instability, I ultimately argue, suggests a move beyond an Afrocentric perspective on identity and traditional tropes of blackness towards a more processual, fluid, and permeable post-black politics.
Keywords: Serote, Mongane Wally, 1944- -- Criticism and interpretation; Duiker, K. Sello -- Criticism and interpretation; Matlwa, Kopano -- Criticism and interpretation; Black people in literature; Race in literature; Protest literature, African (English); Mimesis in literature; Black people -- Race identity -- South Africa; Serote, Mongane Wally, 1944- -- To every birth Its blood; Duiker, K. Sello -- Thirteen cents; Matlwa, Kopano -- Coconut